Design reflections on the integrated development of rural cultural and ecological resources in China - Lisi You; Meijun Liu; Tie Ji; Xiaojing Wu; Ying Li (Humanities & Social Sciences Communications)
Abstract Industrial civilization speeds up the tensions between culture and environment in China’s rural revitalization project. Reflective thinking on the integrated development of rural cultural and ecological resources results from increased concern for balancing cultural preservation with ecological sustainability. This study distinguishes the separation of culture and ecology in the Chinese rural cultural application scene, which often follows a dichotomy instead of a co-evolutionary approach depending on design considerations. The study investigates how design may be a vital instrument in integrating cultural and environmental resources using a systematic, multidisciplinary design process, therefore converting them from stationary, separate entities into modular components with innovation, reconstruction, and market potential. Applying theories of co-evolution and value co-creation, the study creates a thorough framework for the design-driven sustainable transformation of rural areas. The results show that by employing reflective and participatory approaches, design not only closes the gaps between cultural scenes and environmental resources but also stimulates the development of creative economic models such as agritourism complexes and cultural innovation parks. These models show how rural communities may reach ecological sustainability, protect cultural legacy, and improve economic systems. From a design intervention standpoint, the research findings help pertinent policy decisions by providing theoretical insights and practical ideas for rural cultural-ecological integration.